PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Marlin Fitri Daniel Padji; Yuliana Tamu Ina Nuhamara; Darius Imanuel Wadu (Program Studi PGSD Universitas Flores, 2024)
Choosing the right learning model has a big influence on student learning outcomes. In practice, at SMP Negeri 4 Mauliru they tend to still use lecture or conventional learning methods so that student learning outcomes are relatively low. Therefore, reseach was carried out by applying the Project Based Learning (PBL) model. This research aims to see the effect of the PBL model on student mathematics learning outcomes. Learning outcomes are the entire series of activities that have been completed during the learning process, both directly and indirectly, which are then used as a benchmark for determining the level of success achieved by students. This research is quantitative research with an experimental type using a one-group pre-test post-test design. The population in this study were all class VIII students at SMP Negeri 4 Mauliru and the subjects were all class VIIIC students. The instruments used in this research were a pretest and posttest consisting of 5 questions. The data analysis used in this research is descriptive and inferential analysis. The results of this research indicate that there is a significant influence on students' mathematics learning outcomes using the PBL model. This is based on the results of the hypothesis test which shows that the sig (2-tailed) value is 0.000, which means the value is less than 0.05 (< 0.05), so Ha is accepted and H0 is rejected. So it can be concluded that there is an influence of the PBL model on student mathematics learning outcomes.